Singing Style, Vocal Habits, and General Health of Professional Singers - Santos,Sabrina Silva (2019)
Abstract Introduction For the singer, the voice is a medium used to express feelings that capture the listener. Every singing style has specific demands, and a vocal alteration may prevent the singer from meeting them. Objective To compare the singing style, the vocal habits, and the general health data of professional singers. Methods Cross-sectional, quantitative and retrospective study of a survey database. Data on the singing style, the vocal habits, and the health conditions and history of 57 professional singers, 31 female singers and 26 male singers, aged from 19 to 57 years old (average of 32 years old), from a mid-sized town were analyzed Results Therewas a prevalence of female (54 ± 2%) popular singers (91 ± 2%), in the adult age (51 ± 2%), nonsmokers (89 ± 2%), nonusers of alcohol (77 ± 2%), with respiratory problems (53 ± 2%), mainly rhinitis (23 ± 2%), and without other health problems. There was a significant use of alcohol in males (p = 0.010); among the alcohol users, there was a significant presence of respiratory problems (p = 0.046), of pharyngitis/tonsillitis (p = 0.003), and of gastroesophageal reflux (GER) (p = 0.043); there was a significant presence of GER in subjects reporting endocrine problems (p = 0.023), of gastritis (p = 0.023), and of pharyngitis/tonsillitis (p = 0.030). Conclusion There was a predominance of adult professional popular female singers, with complaints of respiratory issues (with a higher prevalence of rhinitis), without other general health issues, of nonsmokers, and of nonusers of alcohol.